Age Differences in the Manifestation of Endurance Ability of Boys Karate Athletes - Svitlana Marchenko; Bohdan Fedotov (Journal of Learning Theory and Methodology)
Objectives.  This research aims to determine the favourable age periods for endurance development among 7-11-year-old pupils who are engaged in initial karate training groups.